A modified Mori–Tanaka approach incorporating filler-matrix interface failure to model graphene/polymer nanocomposites. (15th August 2020) - Sadeghpour, Ebrahim; Guo, Yangbo; Chua, Daniel; Shim, Victor P.W.
Highlights: Study of quasi-static uniaxial loading-unloading tensile response of a PVA-graphene oxide nanocomposite. Identification of interfacial slip between polymer matrix and filler as a significant factor for the stress-strain response. Development of an interfacial slip model using finite elements to simulate filler-matrix interaction when interfacial slip occurs. Incorporation of interfacial slip model into Mori-Tanaka theory to analyze the large deformation stress-strain response of the graphene oxide polymer nanocomposite. Abstract: A novel modified Mori-Tanaka (M-T) approach to modeling the stress-strain response of graphene nanocomposites subjected to large deformation is described. It is hypothesized that slip at the filler-matrix interface occurs, and this limits the stress which can be transferred to the filler through the interface. Although interfacial slip has a significant influence on the mechanical response of polymer nanocomposites, the M-T method, commonly employed to model nanocomposites, does not accommodate this effect. A pseudo-filler phase is defined to represent the filler when interfacial slip occurs, and this is modeled using finite elements to simulate a single filler flake encapsulated by the interface, interacting with the matrix. The stiffness of the pseudo-filler is determined by examination of the variation of stress in the filler when interfacial slip occurs; this interfacial slip model is incorporated into the M-T method. Quasi-static tensile loading and unloading tests were conducted on polyvinyl alcohol (PVA)-graphene oxide (GO) nanocomposite samples, and significant enhancement of the stress-strain response of the nanocomposite was observed by the addition of GO; e.g. a 5 wt% GO addition increases the initial elastic modulus of PVA from 330 MPa to 1.29 GPa. The modified M-T method was used to simulate the stress-strain response of the nanocomposites, and the theoretical results compare well with experimental stress-strain data for both loading and unloading. Graphical abstract: Image, graphical abstract